Nonvolatile Logic‐in‐Memory Computing based on Solution‐Processed CuI Memristor (Adv. Electron. Mater. 11/2022). (10th November 2022) - Li, Bochang; Wei, Wei; Luo, Li; Gao, Ming; Yu, Zhi Gen; Li, Sifan; Ang, Kah‐Wee; Zhu, Chunxiang
Abstract : Nonvolatile Logic‐in‐Memory Computing In article number 2200089, Chunxiang Zhu and co‐workers propose and demonstrate an electrochemical metallization memristor based on a solution‐processed Pt/CuI/Cu structure. Owing to the efficient drift paths provided by Cu vacancies for Cu cations in CuI, very small operating voltages are realized, contributing to the ultralow power consumption. Using CuI memristor arrays, a set of Boolean logic operations and a half adder are implemented.